Pulsed Injections of Metal‐Rich Magmatic Fluids: Key Drivers of Mineralization in a Back‐Arc Basin Hydrothermal System - Xia Zhang; Zhilei Sun; Yachun Cai; Yue Xu; Nengyou Wu; Hong Cao (Geochemistry, Geophysics, Geosystems, 2025)
Abstract Submarine magmatic–hydrothermal systems, where magmatic volatiles and fluids possibly serve as major sources of mineralization elements, have been extensively documented in numerous felsic‐hosted hydrothermal fields. Previous studies have primarily focused on the contribution of magmatic volatiles in such hydrothermal systems. Although evidence has indicated that magmatic fluids have a greater capacity for transporting metals to overlying hydrothermal systems, their specific role in magmatic–hydrothermal systems remains inadequately understood. This study provides compelling evidence for the contribution of metal‐rich magmatic fluid to the Minami–Ensei (ME) hydrothermal system. Pulsed injections of metal‐rich magmatic fluids into the overlying hydrothermal system during mineralization process result in the elevated salinity (6.1–9.7 wt.% NaCl equiv) and δ18O values (1.1–8.0‰) in ME hydrothermal fluids, which are recorded by barite fluid inclusions and oxygen (O) isotope compositions, respectively. Laser‐induced breakdown spectroscopy analysis indicated that the magmatic fluids injected into the ME were likely Fe‐rich. Metal concentrations in magmatic fluids are several orders of magnitude higher than those in hydrothermal fluids generated via leaching, and their contribution to overlying hydrothermal systems can substantially enhance sulfide mineralization efficiency in magmatic–hydrothermal deposits. This study underscores the potential of magmatic–hydrothermal systems as promising targets for future sulfide ore exploration.